Studi Kebijakan Seleksi Koleksi di Perpustakaan Universitas Tarumanagara (Jurnal Adabiya, 2022)
Collection development is very important for libraries as information managers. One of the most decisive stages is collection selection to ensure collection materials are in accordance with the needs and objectives of the library. Collection materials are used to support academic activities, both teaching and research. Collection materials determine the quality of the library because it is able to meet the needs of users. A good library guarantees the advancement of an institution, including the university. This paper analyzes the collection selection policy at the Tarumanagara University Library. The method used is descriptive analysis to get a specific picture based on the data. The results of the study indicate that there is a collection selection policy that is contained in a written collection development policy and has been implemented in accordance with the guidelines made.